Toward Thing-to-Thing Optical Wireless Power Transfer: Metal Halide Perovskite Transceiver as an Enabler - Nguyen, Dinh Hoa; Matsushima, Toshinori; Qin, Chuanjiang; Adachi, Chihaya (Frontiers in Energy Research, 2021)
This paper proposes a novel conceptual system of optical wireless power transfer (OWPT) between objects, which is different from the existing OWPT systems that a single device – an optical transceiver is employed. This optical transceiver, which is capable of both absorbing and emitting light, is fabricated from a metal halide perovskite known for superior features that can help significantly reduce the whole system size and cost. The proposed system contributes to realize a thing-to-thing OWPT network, in which surfaces of objects/things are covered by perovskite transceivers (fully or partially), enabling them to wirelessly charge or discharge from the others.